1987
DOI: 10.1172/jci112941
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface expression of fMet-Leu-Phe receptors on human neutrophils. Correlation to changes in the cytosolic free Ca2+ level and action of phorbol myristate acetate.

Abstract: We have studied how cytosolic free Ca2" ([Ca2+Ii)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 43 publications
0
38
0
1
Order By: Relevance
“…The cells were washed and resuspended (10 7 /ml) in Krebs-Ringer phosphate buffer containing glucose (10 mM), Ca 2ϩ (1 mM), and Mg 2ϩ (1.5 mM) (KRG; pH 7.3). This procedure allows for cells to be isolated with minimal mobilization effects (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were washed and resuspended (10 7 /ml) in Krebs-Ringer phosphate buffer containing glucose (10 mM), Ca 2ϩ (1 mM), and Mg 2ϩ (1.5 mM) (KRG; pH 7.3). This procedure allows for cells to be isolated with minimal mobilization effects (1).…”
Section: Methodsmentioning
confidence: 99%
“…The amount of FPR on the cell surface was determined by incubating the neutrophils with radiolabeled fMLF in the presence or absence of excess unlabeled fMLF as described earlier (1). In short, 100 l of dibutylphthalate mixed with dinonylphthalate (10:3, vol/vol) was layered on top of 10 l of urea (6 M) in Eppendorf tubes; 50 l of [ 3 H]fMLF (8 ϫ 10 Ϫ8 M) together with 50 l of KRG or unlabeled fMLF (4 ϫ 10 Ϫ5 M) in KRG was layered on top of the oil.…”
Section: Methodsmentioning
confidence: 99%
“…7B, neutrophils were primed in their response to Cmp1 by the cytokine TNF-␣, the primed neutrophils produced at least 5 times (measured as peak values) more superoxide anions than did naive neutrophils, and the production reached levels comparable to that induced by fMLF. Previous studies have shown that many neutrophil receptors, including FPR1 and FPR2, are stored in secretory organelles of naive cells (34)(35)(36), and mobilization of FPRs to the cell surface is accompanied with a primed FPR response, suggesting a possible role for granule mobilization in mediating priming.…”
Section: Cmp1 Activates the Phospholipase C-inositol Phosphate 3 (Ip mentioning
confidence: 98%
“…For experiments determining the ability of AAT to act as an inhibitor of LTB 4 BLT1 signaling, healthy control neutrophils (2 3 10 6 cells/ml) were first challenged with PMA (100 ng) for 10 min at 37˚C to increase membrane levels of the BLT1 receptor (60). Cells were then untreated or were treated with LTB 4 (100 nM) in the presence or absence of AAT (27.5 mM) or U-75302 (1 mM) for 10 min or 100 nM NE for 0, 15, or 30 min at 37˚C.…”
Section: Flow Cytometric Assaysmentioning
confidence: 99%